A systematic literature review (SLR) of indoor air quality (IAQ) on occupants’ health and well-being in residential building / Azureen Kharuddin, Asniza Hamimi Abdul Tharim and Asmat Ismail - Kharuddin, Azureen; Abdul Tharim, Asniza Hamimi; Ismail, Asmat (2021)
Air pollution is a major disturbance nowadays. It occurs in not only one country, but even throughout the whole world. Besides, air pollution involves not only one gas, but also a variety of gases that can give an impact on human health and flora and fauna. Hence, this paper aims to review the previous research related to indoor air quality (IAQ) conducted worldwide. A Systematic Literature Review (SLR) was employed in this study to identify, critically appraise, and summarise the previous research findings related to the IAQ. This paper concludes that particulate matter, nitrogen dioxide, and carbon monoxide were the problems that are commonly associated with IAQ as addressed by other researchers. These findings are beneficial to new researchers who intended to conduct a study on the aspect of IAQ.